Bridging pedagogy and practice: Hybrid collaborative learning based lesson study integrated with wahdatul ulum principles for pre-service biology teacher - Jayanti, Ummi Nur Afinni Dwi (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
In an era that requires a balance between theory and practice for effective teaching, pre-service teachers need the skills to design integrated, contextual, and meaningful learning experiences. This study examines the impact of implementing a Hybrid Collaborative Learning-based Lesson Study, oriented toward Wahdatul Ulum, on the lesson planning skills of pre-service biology teachers. The study employs a mixed-method approach with a parallel convergent design. Quantitative data were collected through questionnaires administered to 83 students at the end of the Biology Lesson Planning course at a State Islamic University in North Sumatra, while qualitative data were obtained through semi-structured interviews. The instruments used included Likert scale questionnaires and interview sheets. Data was analyzed using descriptive statistics and thematic content analysis. The analysis that the skills developed include formulating learning indicators and objectives, preparing materials, and designing learning steps in accordance with instructional syntax. Teaching practice also aided students in identifying challenges and learning from peer teaching. These findings suggest that an approach integrating theory, practice, and religious values is effective for developing the pedagogical skills, character, and professionalism of pre-service biology teachers.